Comparison of error control schemes in wireless sensor networks - TIAN Zhen; YUAN Dong-feng; LIANG Quan-quan (Tongxin xuebao)
Energy efficiency analyses of automatic repeat request （ARQ） and forward error correction （FEC） techniques were presented. Chase combining hybrid ARQ （HARQ） was proposed to achieve adaptive error control in wireless sensor networks. Moreover, Chase combining HARQ was compared with ARQ and FEC in terms of energy efficiency based on different communication distances and packet lengths. The simulation result shows that Chase combining HARQ is the optimal scheme on the whole.